Correction to: Questionnaire choice affects the prevalence of recommended physical activity: an online survey comparing four measuring instruments within the same sample - Gerrit Stassen; Kevin Rudolf; Madeleine Gernert; Ansgar Thiel; Andrea Schaller (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.